Competition, Challenge and Change. - Jones, Robert (2014)

(untitled)
A main strategic initiative of Brush Electrical Machines Limited, (Brush), is to continue with the development and growth of the Aftermarket section of their business. This will require the company to build upon their existing customer base and develop new relationships with customers, by delivering value to the customer’s operation as a result of meeting and exceeding their needs.